Effective dose of propofol combined with a low-dose esketamine for gastroscopy in elderly patients: A dose finding study using dixon’s up-and-down method - Zheng, Yuling; Xu, Yafei; Huang, Bixin; Mai, Ying; Zhang, Yiwen; Zhang, Zhongqi (Frontiers in Pharmacology, 2022)
Objective: This study aimed to determine the optimal dose of propofol combined with esketamine to inhibit the response to gastroscopy insertion in elderly patients. Methods: A total of 32 elderly patients (17 males and 15 females, aged 65-80 years) were enrolled in the study with the American Society of Anesthesiologists (ASA) physical status I or II undergoing elective gastroscopy. All patients were administered propofol after an intravenous esketamine at the dosage of 0.3 mg/kg 30 s, the subsequent dose of propofol was determined by the response of the previous patient to gastroscopy insertion (choking, body movement, etc.) using Dixon’s up-and-down method. The initial dose of propofol administered to the first elderly patient was 3.0 mg/kg, and the standard ratio of propofol dose in adjacent patients was 0.9. Seven crossovers were obtained before the conclusion of the study. By using Probit analysis, the median effective dose (ED50), 95% effective dose (ED95), and the corresponding 95% confidence interval (CI) for Propofol were determined. Results: The ED50 of propofol combined with esketamine inhibiting response to gastroscopy insertion in elderly patients were found to be 1.479 mg/kg (95% CI: 1.331 ~ 1.592 mg/kg), and ED95 was found to be 1.738 mg/kg (95% CI: 1.614~2.487 mg/kg). Conclusion: According to the present study, propofol combined with 0.3 mg/kg esketamine is safe and effective for elderly patients undergoing gastroscopy. The ED50 and ED95 doses of propofol inhibiting response to gastroscopy insertion in elderly patients when combined with 0.3 mg/kg esketamine were 1.479 and 1.738 mg/kg, respectively, without apparent adverse effects.